The color of citizenship race, modernity and Latin American / Hispanic political thought - Von Vacano, Diego A., 1970- (New York ; Oxford : Oxford University Press, 2012)
Why is race, a superficial human characteristic, such a potent political phenomenon? Looking to the way that race has been conceived through the tradition of Latin American political thought, 'The Color of Citizenship' examines the centrality of race in the making of modern citizenship.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Mar. 5, 2012).
Keywords: Citizenship -- Latin America -- Philosophy -- History; Race -- Philosophy; Latin America -- Race relations -- Philosophy; Philosophy, Latin American